1987
DOI: 10.1111/j.1365-2311.1987.tb01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition between two parasites of the Florida red scale in Israel

Abstract: 1. During the last decade, the endoparasitic wasp Pteroptrix smithi (Compere) has gradually replaced the ectoparasitic wasp Aphytis holoxanthus DeBach on the Florida red scale, Chrysomphalus aonidum (L.), on citrus in Israel. The studies reported herein were aimed at elucidating some of the mechanisms of this process.2. Aphytis adults detected, and were attracted to hosts containing eggs of Pteroptrix, whereas adults of Pteroptrix did not detect hosts containing eggs of Aphytis. In this extrinsic aspect of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…tend to be more vulnerable to pesticides because they develop externally. In the parasitoid complex of Florida red scale in Israel, A. holoxanthus was generally more abundant than Pteroptrix smithi (Compere), but the relative abundance was reversed when malathion was applied (Steinberg et al, 1987). Encarsia berlesei may also be more vulnerable to pesticides than P. orientalis because its peak emergence period in June and July coincides with a period of frequent pesticide treatment.…”
Section: Biological Controlmentioning
confidence: 97%
See 1 more Smart Citation
“…tend to be more vulnerable to pesticides because they develop externally. In the parasitoid complex of Florida red scale in Israel, A. holoxanthus was generally more abundant than Pteroptrix smithi (Compere), but the relative abundance was reversed when malathion was applied (Steinberg et al, 1987). Encarsia berlesei may also be more vulnerable to pesticides than P. orientalis because its peak emergence period in June and July coincides with a period of frequent pesticide treatment.…”
Section: Biological Controlmentioning
confidence: 97%
“…Aphytis proclia was the probable victor in these contests (PAP, unpublished data), and therefore caused mortality of E. berlesei. All species of Aphytis are ectoparasitoids, and are often competitively superior to endoparasitoids in the same complex (Kennett et al, 1966;Steinberg et al, 1987).…”
Section: Parasitoid Interactionsmentioning
confidence: 99%
“…It is also argued now (Bakker et al 1985, van Alphen and Visser 1990) that intraspecific discrimination is not always an advantageous strategy. The detection by parasitoids of competitors within a host generally appears to require host necrosis provoked by the first infection (Strand 1986, Steinberg et al 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Interspecific host discrimination is relatively rarely reported, and in studies where rejection of hosts parasitized by another parasitoid species has been shown, this discrimination is time-dependent (Steinberg et al, 1987 ;Strand, 1986 ;Vinson, 1972 ;Wylie, 1970Wylie, , 1971 ; van Aiphen & van Strien-van Liempt, unpubl, data). Other endoparasitoids of H. virescens have been reported not to discriminate interspecifically.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where rejection of hosts parasitized by another parasitoid species has been shown, this rejection is more likely to be due to a severely changed physiological condition of the host, rather than to the recognition of a specific mark (Steinberg et al, 1987 ;Strand, 1986;Vinson, 1972;Wylie, 1970Wylie, , 1971; van Alpben & van Strien-van Liempt, in preparation). An exception was reported by Vet et al (1984) who determined that Asobara tabida (Nees) and Asobara rufescens (Foerster) were capable of discriminating against hosts recently parasitized by females of the other species.…”
Section: Discussionmentioning
confidence: 99%